Nickel Sensitivity Is Associated with GH-IGF1 Axis Impairment and Pituitary Abnormalities on MRI in Overweight and Obese Subjects - Risi, Renata; Masieri, Simonetta; Poggiogalle, Eleonora; Watanabe, Mikiko; Caputi, Alessandra; Tozzi, Rossella; Gangitano, Elena; Masi, Davide; Mariani, Stefania; Gnessi, Lucio; Lubrano, Carla (International journal of molecular sciences, 2020)
Nickel (Ni) is a ubiquitous metal, the exposure of which is implied in the development of contact dermatitis (nickel allergic contact dermatitis (Ni-ACD)) and Systemic Ni Allergy Syndrome (SNAS), very common among overweight/obese patients. Preclinical studies have linked Ni exposure to abnormal production/release of Growth Hormone (GH), and we previously found an association between Ni-ACD/SNAS and GH-Insulin-like growth factor 1 (IGF1) axis dysregulation in obese individuals, altogether suggesting a role for this metal as a pituitary disruptor. We herein aimed to directly evaluate the pituitary gland in overweight/obese patients with signs/symptoms suggestive of Ni allergy, exploring the link with GH secretion; 859 subjects with overweight/obesity and suspected of Ni allergy underwent Ni patch tests. Among these, 106 were also suspected of GH deficiency (GHD) and underwent dynamic testing as well as magnetic resonance imaging for routine follow up of benign diseases or following GHD diagnosis. We report that subjects with Ni allergies show a greater GH-IGF1 axis impairment, a higher prevalence of Empty Sella (ES), a reduced pituitary volume and a higher normalized T2 pituitary intensity compared to nonallergic ones. We hypothesize that Ni may be detrimental to the pituitary gland, through increased inflammation, thus contributing to GH-IGF1 axis dysregulation.